Brexit, foreign investment and employment: some implications for industrial policy?. Issue 2 (3rd April 2019) - Bailey, David; Driffield, Nigel; Kispeter, Erika
ABSTRACT: Inward investment in the UK is likely to be negatively impacted in a number of ways in the event of a 'hard Brexit' via tariff barriers, but even 'softer' forms of Brexit such as the current potential agreement are likely to cause customs delays, limits to the ability of firms to relocate staff, and to coordinate 'servitization' activities. In addition are the the negative impacts of currency depreciation. In the context of already existing job market polarisation, inward investment flows in advanced manufacturing, food technology and financial services, which can bring 'good quality' jobs, are especially vulnerable under Brexit to frictions in global value chains. After highlighting the case of the auto industry, the paper moves on to stress the links between inward investment, employment restructuring and job quality given the employment opportunities foreign firms create.